2010
DOI: 10.1016/j.vetimm.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Bluetongue virus infection activates bovine monocyte-derived macrophages and pulmonary artery endothelial cells

Abstract: Bluetongue virus (BTV) is the cause of bluetongue (BT), an emerging, arthropod-transmitted disease of ungulates. The cellular tropism of BTV in ruminants includes macrophages, dendritic cells and endothelial cells (EC), and fulminant infection is characterized by lesions consistent with those of so-called viral hemorrhagic fevers. Specifically, BT is characterized by vascular injury with hemorrhage, tissue infarction and widespread edema. To further investigate the pathogenesis of vascular injury in BT, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 26 publications
2
40
0
2
Order By: Relevance
“…Nevertheless, the excessive production of iNOS, and subsequent high levels of NO during viral infections may have negative effects, acting with other damaging oxidants to promote excessive inflammation or induce apoptosis, as it has been described in influenza virus infection 43. As it has been described in the pathogenesis of viral hemorrhagic fevers 15, 44, 45, the overproduction of iNOS and pro-inflammatory cytokines in BTV infected tissues could contribute to the pathology of this disease-causing vasodilatation, increase of leukocyte adhesion and thrombus formation, and increase of vascular permeability of endothelial cells with subsequent tissue edema 39, 46.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Nevertheless, the excessive production of iNOS, and subsequent high levels of NO during viral infections may have negative effects, acting with other damaging oxidants to promote excessive inflammation or induce apoptosis, as it has been described in influenza virus infection 43. As it has been described in the pathogenesis of viral hemorrhagic fevers 15, 44, 45, the overproduction of iNOS and pro-inflammatory cytokines in BTV infected tissues could contribute to the pathology of this disease-causing vasodilatation, increase of leukocyte adhesion and thrombus formation, and increase of vascular permeability of endothelial cells with subsequent tissue edema 39, 46.…”
Section: Discussionmentioning
confidence: 91%
“…Besides the induction of pro-inflammatory cytokines observed in serum and tissues of BTV infected ruminants, it has been also reported that BTV infection of sheep led to enhance transcription of iNOS in peripheral blood mononuclear cells and regional lymphoid organs 42. Furthermore, in vitro studies provided evidence that cytokines and other vasoactive substances produced in macrophages potentially contributed to vascular injury in BTV-infected ruminants 39. The IFNAR(-/-) mouse model reproduced in vivo the increase expression of iNOS in BTV-4(M) infected tissues.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations